Enhancing peer acceptance of children with learning difficulties: classroom goal orientation and effects of a storytelling programme with drama techniques. Issue 5 (28th May 2017) - Law, Yin-kum; Lam, Shui-fong; Law, Wilbert; Tam, Zoe W. Y.
Abstract: Peer acceptance is an important facilitator for the success of inclusive education. The aim of the current study is twofold: (1) to examine how classroom goal orientation is associated with children's acceptance of peers with learning difficulties; and (2) to evaluate the effectiveness of a storytelling programme with drama techniques on children's acceptance of peers with learning difficulties. The participants were 86 Grade 3 students from a Hong Kong primary school, randomly assigned to an experimental group ( n = 45) and a control group ( n = 41). The findings indicated that the more the students perceived that their classroom was performance-approach oriented, the less they would accept their peers with learning difficulties in doing things together. After the intervention, the students in the experimental condition, compared to their counterparts in the control group, were more likely to render financial assistance and have affective acceptance to their peers with learning difficulties.